PENGUATAN AKHLAK SANTRI BERBASIS KITAB TA'LIM AL-MUTA'ALLIM ERA SOCIETY 5.0 DI PONDOK PESANTREN BAITUL HIKMAH TEMPUREJO JEMBER - Fatimatus Zahro; Fathor Rahman (EDUCATIONAL : Jurnal Inovasi Pendidikan & Pengajaran, 2026)
ABSTRACT Social transformation in the Society 5.0 era requires Islamic educational institutions to strengthen moral character development amid the increasing exposure to digital content that is not always aligned with Islamic values. Although numerous studies have examined character education in Islamic boarding schools, research specifically investigating moral character reinforcement strategies as a response to the challenges of Society 5.0 remains limited. This study aims to examine the moral values instilled, the reinforcement methods employed, and their impact on students at Baitul Hikmah Islamic Boarding School, Tempurejo, Jember, during the 2025/2026 academic year. This research employed a descriptive qualitative approach, with data collected through observation, in-depth interviews, and documentation. The data were analyzed through data reduction, data display, and conclusion drawing. The findings reveal that moral character reinforcement focuses on the values of honesty, trustworthiness, responsibility, dedication, and ta’dzim (respect), which are internalized through role modeling, structured habituation, disciplinary evaluation, and controlled use of digital technology. The observed impacts include improved consistency in worship practices, greater respect for educators, enhanced social awareness, and stronger student discipline. The novelty of this study lies in its analysis of moral character reinforcement that integrates character development based on the Ta’limul Muta’allim text with strategies for managing digital challenges in the Society 5.0 era. This study highlights that a holistic and sustainable Islamic boarding school education system can serve as an effective model for strengthening character education grounded in Islamic values while remaining relevant to technological advancements and contemporary social changes. ABSTRAK Transformasi sosial pada era Society 5.0 menuntut lembaga pendidikan Islam untuk memperkuat pembinaan akhlak di tengah meningkatnya paparan konten digital yang tidak selalu sejalan dengan nilai-nilai keislaman. Meskipun berbagai penelitian telah membahas pendidikan karakter di pesantren, kajian yang secara khusus mengkaji strategi penguatan akhlak sebagai respons terhadap tantangan Society 5.0 masih relatif terbatas. Penelitian ini bertujuan mengkaji nilai-nilai akhlak yang ditanamkan, metode penguatan yang diterapkan, serta dampaknya terhadap peserta didik di Pondok Pesantren Baitul Hikmah Tempurejo Jember tahun 2025/2026. Penelitian menggunakan pendekatan kualitatif deskriptif dengan pengumpulan data melalui observasi, wawancara mendalam, dan dokumentasi yang dianalisis melalui reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa penguatan akhlak berfokus pada nilai kejujuran, amanah, tanggung jawab, dedikasi, dan ta’dzim yang diinternalisasikan melalui keteladanan, pembiasaan terstruktur, evaluasi kedisiplinan, dan pengendalian penggunaan teknologi digital. Dampak yang terlihat meliputi meningkatnya konsistensi ibadah, sikap hormat kepada pendidik, kepedulian sosial, dan kedisiplinan santri. Kebaruan penelitian ini terletak pada analisis penguatan akhlak pesantren yang mengintegrasikan pembinaan karakter berbasis kitab Ta’limul Muta’allim dengan pengelolaan tantangan digital era Society 5.0. Penelitian ini menegaskan bahwa sistem pendidikan pesantren yang holistik dan berkelanjutan dapat menjadi model penguatan karakter berbasis nilai Islam yang tetap relevan dalam menghadapi perkembangan teknologi dan perubahan sosial kontemporer.